Tanah untuk Masyarakat Ekonomi Lemah - Abdurrahman Abdurrahman (Universitas Syiah Kuala, 2012)
ABSTRACT: In order to achieve welfare, everyone has a right to have and own land individually including the right n it. However, the reality of Indonesian shows that the gap of ability to have land causing the low income is not able to compete the have. In terms of protecting the have not, the state has a power to interfere as stated in the Land Act as to be a legal basis for it. There is an explicit rule regulating the protection towards the low-income people as mentioned in Article 11 of the Act and there are also regulations substantially in Articles 7, 9, 17 of the Act. In addition, there is a rule for implementation of the Act but Is only limited to the protection of the have not in owning he land for farming and there is no regulation on the ownersip for the land in city and non-farming land. The availability such rules in not balanced with the implementation; hence there are many people that are low-income category have not had the land yet. Land for Low Income People